Discurso egocéntrico frente a discurso cooperativo: Hombres, mujeres y verbos - López González, Antonio María (Studia Romanica Posnaniensia, 2004)
D. Tannen (1990) defines women's cooperative discourse versus men's egocentric discourse. Relating to the use of verbs, both kinds of discourse are characterized by a different use of the persons of conjugation, a lexically and semantically different selection of verbs and also diverse syntactic use of verbs. In this article, I show how both kinds of discourses appear in the broadcasting media, focusing on the use of verbs.